2019
DOI: 10.1021/acs.jafc.9b03335
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Mulberry Fruit (Morus alba L.) Protects against Palmitic-Acid-Induced Hepatocyte Lipotoxicity by Activating the Nrf2/ARE Signaling Pathway

Abstract: This study was aimed to investigate the protective effects of three different mulberry fruit polysaccharide fractions (MFP-I, MFP-II, and MFP-III) against palmitic acid (PA)-induced hepatocyte lipotoxicity and characterize the functional polysaccharide fraction using gel permeation chromatography, high-performance liquid chromatography, Fourier transform infrared spectroscopy, and nuclear magnetic resonance analyses. MFP-I, MFP-II, and MFP-III were isolated from mulberry fruit by stepwise precipitation with 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 47 publications
0
37
1
Order By: Relevance
“…MBEs in HFD-fed male Sprague-Dawley rats prevented non-alcoholic fatty liver disease (NAFLD) by downregulating lipid/cholesterol homeostasis-related genes (FAS, ACC, GPAT, and SREBP-1) and suppressing the lipid oxidation biomarkers MDA and 4-hydroxynonenal [ 105 , 106 ]. Hu et al [ 275 ] demonstrated that MBE increased nuclear factor erythroid-2-related factor 2 (Nrf2) phosphorylation and nuclear translocation, activating the Nrf2/antioxidant response element signaling pathway, which increased quinone oxidoreductase 1, HO-1, and NAD(P)H expression and promoted antioxidant enzymatic activities, thus protecting hepatocytes against palmitic acid-induced lipo-toxicity and oxidative stress.…”
Section: Mulberriesmentioning
confidence: 99%
“…MBEs in HFD-fed male Sprague-Dawley rats prevented non-alcoholic fatty liver disease (NAFLD) by downregulating lipid/cholesterol homeostasis-related genes (FAS, ACC, GPAT, and SREBP-1) and suppressing the lipid oxidation biomarkers MDA and 4-hydroxynonenal [ 105 , 106 ]. Hu et al [ 275 ] demonstrated that MBE increased nuclear factor erythroid-2-related factor 2 (Nrf2) phosphorylation and nuclear translocation, activating the Nrf2/antioxidant response element signaling pathway, which increased quinone oxidoreductase 1, HO-1, and NAD(P)H expression and promoted antioxidant enzymatic activities, thus protecting hepatocytes against palmitic acid-induced lipo-toxicity and oxidative stress.…”
Section: Mulberriesmentioning
confidence: 99%
“…Oral feeding of mulberry fruit to rats shows a decrease in the levels of liver enzymes, hydroxyproline, hyaluronidase, ALT (Alanine aminotransferase), AST (aspartate aminotransferase) and collagen type 3 (Li et al, 2016). Further, Hu et al (2019) isolated the three different mulberry fruit polysaccharide fractions (MFP-I, MFP-II, and MFP-III) through stepwise precipitation with 30%, 60%, and 90% ethanol, respectively, and evaluated their protective efficacy against palmitic acid (PA)induced hepatocyte lipotoxicity. It was observed among all the MFPs, MFP-II significantly reduced PA-induced hepatic lipotoxicity at 0.1 and 0.2 mg/mL while other two (MFP-I and MFP-III) displayed weak protection.…”
Section: Neuroprotectivementioning
confidence: 99%
“…These active components contain reactive oxygen species (ROS) scavengers [4,9,10]. Substantial previous evidences indicated that MLs could be a potential functional ingredient for the production of healthy foods [5][6][7]. However, the leaves of black mulberry varieties are generally discarded because they are planted only for fruit, and the leaves are not advisable for use as food even for silkworms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mulberry leaves (MLs) have been recognized as edible with medicinal properties owing to their phytochemical content [ 4 ]. Phytochemical studies have shown that MLs are a rich source of a variety of constituents, including flavonoids [ 3 , 5 ], polysaccharides [ 1 , 6 ], alkaloids [ 7 ], and 1-deoxynojirimycin [ 8 ]. Besides, several different flavonol (i.e., quercetin and kaempferol) glycosides have been reported as antioxidant constituents in MLs.…”
Section: Introductionmentioning
confidence: 99%